2022
DOI: 10.1101/2022.03.24.485616
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The actin assembly requirements of the formin Fus1 to build the fusion focus

Abstract: Formins form the largest family of actin filament nucleators and elongators, involved in the assembly of diverse actin structures. Actin filament nucleation and elongation activities reside in the formin homology 1 (FH1) and FH2 domains, common to all formins. However, the rate of these reactions varies between formins by at least 20-fold. Typically, each cell expresses several distinct formins, each contributing to the assembly of one or several actin structures, raising the question of what confers each form… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…We previously showed that Fus1 function during cell fusion cannot be fulfilled by either of the other two fission yeast formins, For3 and Cdc12 [11]. However, chimeric proteins containing the Fus1 regulatory N-terminus (called Fus1N below) and the actin nucleating FH1-FH2 domains of For3 or Cdc12 partially rescued fus1Δ defects, indicating an important role for Fus1N.…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that Fus1 function during cell fusion cannot be fulfilled by either of the other two fission yeast formins, For3 and Cdc12 [11]. However, chimeric proteins containing the Fus1 regulatory N-terminus (called Fus1N below) and the actin nucleating FH1-FH2 domains of For3 or Cdc12 partially rescued fus1Δ defects, indicating an important role for Fus1N.…”
Section: Resultsmentioning
confidence: 99%